Minority language promotion, protection and regulation the mask of piety - Williams, Colin H.; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2013)
This is an analysis of the promises and contradictions surrounding contemporary minority language policy. It draws on theoretical and real-world perspectives and interviews with key players within European institutions together with field work undertaken principally in Ireland, Scotland, Wales, the Basque Country, Catalonia and Canada.
Keywords: Linguistics; Applied linguistics; Historical linguistics; Sociolinguistics; Linguistics; Historical Linguistics; Sociolinguistics; Applied Linguistics